OPTIMALISASI NILAI ILUMINASI DENGAN SKYLIGHT DAN MATERIAL TRANSPARAN UNTUK BANGUNAN DERET-BERTINGKAT PADA RUKO GAIA DI AYODHYA, ALAM SUTERA, TANGERANG - Felisitas Devina D; Ariani Mandala (Riset Arsitektur (RISA), 2022)
Abstract - Multi-story row buildings such as shophouses have problems in accommodating the need for natural lighting due to the linear typology of the building, limitations in making side openings, and consisting of two or more floors. This typology of buildings results in an uneven distribution of light, especially in the middle to the back of the building and on floors other than the top floor. One effort to incorporate natural light or daylight into the elongated shophouse building is to use top lighting. However, the existence of the top lighting does not allowing light to reach the floor other than the top floor of the shophouse due to the obstruction of the floor surface.Transparent materials such as glass allow higher light transmission than opaque materials, so using glass materials can increase the illumination of the space behind the glass. The purpose of this study was to assess the suitability of the illumination level in Ruko Gaia's natural lighting design to the values ​​of Daylight Factor (DF), Spatial Daylight Autonomy (sDA), and Annual Sunlight Exposure (aSE) according to the BREEAM and IES LM-83-12 standards, to examine the effect of changing the position of the stair-skylight and the use of transparent materials on the floor-stairs plane to the illumination level, as well as optimizing the design to increase the DF value according to the standards used. The research begins by evaluating the illumination level of Ruko Gaia’s natural lighting design. By conducting alternative simulations, an assessment will be made to see the effect of changing the position of the skylight-stairs and the use of transparent materials on the floor-stairs plane to the building’s illumination level. If the resulting illumination level has not reached the specified standard, optimization is carried out by increasing the Visible Transmittance value or adding skylight dimensions. The method used is quantitative in the form of evaluation of planning designs and alternative simulations. The theories and data for the Ruko Gaia were collected from literature studies, websites, brochures, and property agents, as well as simulation data processing with SketchUp and Lightstanza software. Based on the evaluation, the illumination level at the Ruko Gaia has not met the BREEAM standard of the DF value in overcast sky conditions, especially on the ground floor. Various alternative studies have concluded that although increasing the DF value, changing the position of the skylights and the use of transparent floors have not resulted in the DF value according to the BREEAM standard. Optimization of the DF value can be achieved by increasing the VLT value or increasing the dimensions of the skylight. Key Words: Multi-story row building, natural lighting, daylight, skylight, transparent material, illumination level, Daylight Factor